(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article the national mentality relevance of research to select the vector of development. Analysis of the role of the citizens’ national identity is important for the implementation of domestic policy mechanisms. It also involves the identification of the transformation features of national mentality, taking into account the process of modernization. Key words: national mentality, national identity, modernization, Kazakhstani identity, unity, education, information society.